Supervised Brain Tumor Segmentation Based on Gradient and Context-Sensitive Features - Zhao, Junting; Meng, Zhaopeng; Wei, Leyi; Sun, Changming; Zou, Quan; Su, Ran (Frontiers in Neuroscience, 2019)
Gliomas have 2 the highest mortality rate and prevalence among the primary brain tumors. In this study, we proposed a supervised brain tumor segmentation method which detects diverse tumoral structures of both high grade gliomas and low grade gliomas in magnetic resonance imaging (MRI) images based on two types of features, the gradient features and the context-sensitive features. Two-dimensional gradient and three-dimensional gradient information was fully utilized to capture the gradient change. Furthermore, we proposed a circular context-sensitive feature which captures context information effectively. These features, totally 62, were compressed and optimized based on an mRMR algorithm, and random forest was used to classify voxels based on the compact feature set. To overcome the class-imbalanced problem of MRI data, our model was trained on a class-balanced region of interest dataset. We evaluated the proposed method based on 2015 Brain Tumour Segmentation Challenge database, and the experimental results show a quite competitive performance.